2020
DOI: 10.1007/s10493-020-00552-9
|View full text |Cite
|
Sign up to set email alerts
|

Males cannibalise and females disperse in the predatory mite Phytoseiulus persimilis

Abstract: Cannibalism is a widespread phenomenon in nature, often occurring when food is scarce, for example among predators that have overexploited a local prey population. Instead of cannibalising, predators can disperse, thereby avoiding being cannibalised or cannibalising related conspecifics, which results in inclusive fitness loss. Theory on prey exploitation in ephemeral predator-prey systems predicts that predators may be selected to display prudent predation by dispersing early, thus saving food for their remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…For example, females have higher energy requirements than males, because reproduction is costly (Harshman & Zera, 2007) and we can therefore expect that females and males might have different exploitation strategies. Indeed, a previous study has shown that females of P. persimilis disperse earlier than males when food is limited (Revynthi et al, 2020). Similar behavior was observed in the current and previous population dynamics experiments (Revynthi et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For example, females have higher energy requirements than males, because reproduction is costly (Harshman & Zera, 2007) and we can therefore expect that females and males might have different exploitation strategies. Indeed, a previous study has shown that females of P. persimilis disperse earlier than males when food is limited (Revynthi et al, 2020). Similar behavior was observed in the current and previous population dynamics experiments (Revynthi et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, a previous study has shown that females of P . persimilis disperse earlier than males when food is limited (Revynthi et al, 2020 ). Similar behavior was observed in the current and previous population dynamics experiments (Revynthi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%